Direct Percutaneous Mitral Annuloplasty in Patients With Functional Mitral Regurgitation: When and How - Tomasz Gasior (Frontiers in Cardiovascular Medicine, 2019)
Mitral regurgitation (MR) is a frequent valvular disease among patients deemed too high risk for surgery. Echocardiography along with CT is the primary diagnostic tool for MR and offers a comprehensive 3D assessment in patient selection and screening for the optimal treatment method. The direct percutaneous mitral annuloplasty addresses the underlying mechanisms of functional MR with a less invasive, catheter-based approach. The here-described techniques proved a sufficient safety profile, delivered significant MR reduction in most of the cases, and were associated with a notable improvement of symptoms. Although long-term outcome assessment is needed to support these early reports, the percutaneous mitral annuloplasty is likely to set a new standard of treatment in the forthcoming future.